INNOVATION AND SUCCESS: PERCEPTIONS, ATTITUDES AND PRACTICES OF YOUNG FARMERS - Maria G. BOTSIOU; Stavriani KOUTSOU; Vassilios DAGDILELIS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The adoption of innovations in business refers to a set of practices and actions which can contribute decisively to the successful development and progression of the enterprise. According to the National Development Low 3299/2004 (GR), innovation is an applied use of knowledge in the production and marketing of new or improved products, processes and services that find immediate productive, utilitarian and commercial application. Innovative practices and operations are an integral part of the organizational culture of the enterprise, and the result of the underlying assumptions and values of the operator itself. In other words, the mentality of the entrepreneur is the one that leads to the application of innovative practices in the business, and this mentality comprises of his beliefs, values and assumptions. The antonym of innovation is “archaism and routine”, and that is why innovation is facing fierce resistance. In the agricultural sector, innovation is a set of practices associated with the organization, producing innovative products, innovative production practices, new technologies for the control and organization of production, and marketing innovations. The evaluation of firm performance, growth and success, linked to, financial measures as growth, profit and turnover and nonfinancial measures such as autonomy and job satisfaction. These two evaluative metrics, financial and non financial measures, are distinguished by the fact that the first relates to perfectly distinct and measurable criteria, while the second to more indistinct as it relates to quality indicators for the investigation of which requires the use of qualitative research tools. In this sense, the effective investigation of farmers’ attitudes on the concept of a successful farmer can be performed using qualitative research tools. While success requires active towards innovation, agribusiness face difficulties in this, as indeed other small companies in other sectors. In this paper, the innovative practices of young farmers are explored, and also their attitudes and perceptions toward success. For this purpose, the case of 9 young farmers, which are professionally active at the Prefecture of Kilkis (Central Macedonia, GR), is studying. The sample size retrieved from the combine of two separate researches that took place in Kilkis, at deferent periods. The first study conduced in 2009 with a structured questionnaire tool, on a sample size of 110 young farmers; its objective was to identify the innovation profile of these farmers, and the results has already been published in Koutsou and Partalidou (2012). The second research was conducted in 2012 with the tool of in-depth interview to 29 young farmers; its objective was to detect the perceptions and attitudes about the successful farmer concept, and the results have not been published yet. Content analysis was the tool that used for the interviews’ study. The results designate two groups of farmers. The first group refers to these farmers who occurs success as a result of endogenous factors, such as the farmer’s personality, skills, and abilities, and these farmers, according to 2009’s research, are innovators or dormant. The second group, refers to those farmers who occurs success as a result of exogenous factors, such as God or weather, and combining their answers with the 2009’ results, these farmers are conservational.